Implementation of the Teacher Training for Classroom Management - Mandal, Ram Babu (Academic Voices: A Multidisciplinary Journal, 2018)
The main objectives of this study are to investigate the challenges in implementation of teacher training for classroom management, and to explore the strategies of teacher training for classroom management to promote students learning. In the process of collecting data, unstructured interview was taken. The major finding of this study is teacher training is not implemented effectively in the classroom. It is found that there are various difficulties faced by the teachers to implement methods, skills and techniques in the classroom what they have got from training. Thus, for effective implementation of teacher training, the teachers, administration and all the concerned authorities should be responsible.